Handbook of research on cyber law, data protection, and privacy - Dewani, Nisha Dhanraj, 1985-; Khan, Zubair Ahmed, 1985-; Agarwal, Aarushi, 1988-; Sharma, Mamta, 1974-; Khan, Shaharyar Asaf, 1983- (Information Science Reference, (an imprint of IGI Global), 2022)
"This handbook examines the legislations on internet, data security and their effects on user engagement and cyber-crime while contextualizing the inter- relationship between technology and law and addressing the need for additional regulations to safeguard user identification, data and privacy"--